Marketing Approach in Non-Manufactured Somali Product - Faaiso, Timiro; Sareeya, Shacni (Journal of Asian Multicultural Research for Economy and Management Study, 2022)
This study intends to create and assess market-driven value chain management solutions by using a comprehensive marketing strategy to identify the primary bottlenecks and opportunities in the cattle value chain. The effectiveness of these measures will be determined. Additionally, ideas for changing the non-manufactured stock value chain and strengthening quality control are reviewed in order to enhance the cluster’s overall performance. Infrastructure development for non-manufactured commodities has a variety of objectives, including enhancing post-harvest processing facilities, meeting quality criteria, and boosting the non-manufactured stock trading system’s competitiveness